Proceedings of the 2015 Annual Conference on Genetic and Evolutionary Computation 2015
DOI: 10.1145/2739480.2754736
|View full text |Cite
|
Sign up to set email alerts
|

Devising Effective Novelty Search Algorithms

Abstract: Novelty search is a state-of-the-art evolutionary approach that promotes behavioural novelty instead of pursuing a static objective. Along with a large number of successful applications, many different variants of novelty search have been proposed. It is still unclear, however, how some key parameters and algorithmic components influence the evolutionary dynamics and performance of novelty search. In this paper, we conduct a comprehensive empirical study focused on novelty search's algorithmic components. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
109
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(109 citation statements)
references
References 36 publications
0
109
0
Order By: Relevance
“…Thus there is consistent pressure to diverge, meaning mechanisms that enhance the ability to diverge can hitchhike along with the divergences they enable. Furthermore, because divergent algorithms like novelty search and MAP-Elites are designed to simultaneously maintain many distinct lineages (Lehman et al, 2012;Gomes et al, 2015;Nguyen et al, 2015), evolvable lineages can therefore distinguish themselves by consistently producing novelty. In this way, divergent selection systematically aligns with evolvability.…”
Section: Divergent Selection and Evolvabilitymentioning
confidence: 99%
“…Thus there is consistent pressure to diverge, meaning mechanisms that enhance the ability to diverge can hitchhike along with the divergences they enable. Furthermore, because divergent algorithms like novelty search and MAP-Elites are designed to simultaneously maintain many distinct lineages (Lehman et al, 2012;Gomes et al, 2015;Nguyen et al, 2015), evolvable lineages can therefore distinguish themselves by consistently producing novelty. In this way, divergent selection systematically aligns with evolvability.…”
Section: Divergent Selection and Evolvabilitymentioning
confidence: 99%
“…Specifically, replacing objective search with the search for behavioral diversity in controller evolution (Moriguchi and Honiden, 2010;Mouret and Doncieux, 2012;Lehman et al, 2013;Gomes et al, 2015) has been demonstrated to boost the quality of evolved behaviors across a range of simulated (Lehman and Stanley, 2011a;Mouret and Doncieux, 2012;Gomes et al, 2016) and physical (Cully et al, 2015;Cully and Mouret, 2016) ER tasks.…”
Section: Introductionmentioning
confidence: 99%
“…However, current empirical data indicate that for controller evolution to solve complex collective behavior tasks, then neither objective nor nonobjective-based search performs well (evolves high-quality behaviors). Rather, recent research results indicate that hybridizing these two search approaches facilitates the evolution of the high-quality behaviors (Gomes and Christensen, 2013b;Gomes et al, 2013Gomes et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations